Using a flexible electric heating element as a heating device for biogas reactors - Spodoba М.; Spodoba О. (Energy and Automation, 2024)
The article is devoted to the issue of research on the influence of the mass-dimensional characteristics of the combined mixing and electric heating system on the amount of heat released during its cooling. The main hypothesis of the work is that due to the use of the amount of heat accumulated by the combined system of mixing and electric heating during operation, it will be possible to save energy for heating the substance in the reactors. Savings arise due to an increase in the duration between the cycles of turning on the heating device. The article presents the results of numerical studies at different temperatures of the electric heating element, reactor volumes, and mass-size characteristics of the combined system. The dependence of the change in the amount released during cooling of the combined mixing and electric heating system on the mass and dimensional characteristics of the system, the volume of the biogas reactor and the temperature of the heating element was established. The obtained results can be used in the design and construction of systems of mixing and electric heating of the substrate in biogas reactors and combined with an automatic control system. The established dependencies increase the profitability of biogas production and reduce the cost of 1 m3 of generated gas, due to the reduction of energy costs for maintaining the temperature and hydrodynamic conditions necessary for anaerobic fermentation to proceed. Key words: energy, heating, mixing, flexible electric heater, biogas reactor, thermodynamic equilibrium